Implementasi Scrum dalam Perancangan Aplikasi Pembelajaran Budaya Nusantara berbasis Mobile - Tri Agustina Nugrahani; Karina Nine Amalia (Faculty of Computer Science, University of Jember, 2022)
Learning in the field of archipelago insight is very important for the younger generation. The insight of the Indonesian archipelago has a lot of diversity, namely national anthems, regional songs, regional traditional clothes, traditional musical instruments, etc. With the development of technology, the introduction insight into the archipelago can be supported by various innovations. One of the innovations is to create a mobile-based application for learning in field of archipelago insights. This learning is done by designing a mobile-based application. This mobile-based application is the result of a design based on the needs of teachers and parents. Based the results of the application design implemented using Scrum, there are 3 roles, namely super admin, teacher and student. There are 6 main features that can be accessed by students, namely being able to work on games about the national anthem, regional songs, regional traditional clothing, traditional musical instruments, heroes and assessment results. From the product backlog that has been compiled, there are agreed tasks and definitions of done (DoD) of application features. All of the feature implementations are in accordance and have been done with the agreed DoD. It is hoped that this design can help students be active and broaden the cultural insights of the archipelago.